Reliving the Music in the Journeys of Nuestra Señora de la Paz Y Buen Viaje: Aspects and Impressions of Antipolo Baroque to Twentieth Century Manila - Brillantes-Silvestre, Ma. Patricia (Musika Jornal; No 5 (2009), 2011)
None